Impact of Pre-Operative Severity on Post-Operative Functional Outcomes in Patients with Cervical Myelopathy: A Comparative Analysis Using the Nurick Scale: Outcomes of Cervical Myelopathy Using the Nurick Scale - Shakeel, Muhammad; Afzal, Waseem; Shafique, Waleed Bin; Qasmi, Shahzad Ahmad; Mehmood, Asad Ullah; Inam, Shahzad (Pakistan Journal of Health Sciences, 2024)
Cervical myelopathy pertains to the compression of the spinal cord in the neck region. The disease is debilitating in nature, and most cases require surgical intervention to avoid further nerve interference. However, the ability of preoperative myelopathy classification to accurately predict superlative postoperative outcomes remains unknown. Objective: To assess the functional outcomes following surgery in patients diagnosed with cervical myelopathy while considering their preoperative Nurick grade. Methods: A retrospective cohort study was conducted on a cohort of 80 patients diagnosed with cervical myelopathy that underwent surgical intervention in the hospital. The study reviewed and analyzed the demographic data and recorded the type of surgery among other factors such as follow-up duration. Statistical analysis was conducted using SPSS version 26.0 and a comparative test for correlation with respect to pre and post-surgery Nurick grades was done using cross-tabulation. Results: Among 38.75% of cases, surgery was performed on the anterior. A notable improvement in the post-surgery Nurick grade was observed with significant improvement noted in patients with higher preoperative classification. The results had a profound correlation between the two grades before and after surgery as analyzed statistically having a p-value of 0.00. Conclusions: Surgical treatments have proven to be quite effective in improving functional outcomes for individuals diagnosed with cervical myelopathy. Patients who had less severe or milder neurological deficits before the surgery experienced the most significant improvement after the procedure. These findings emphasize the significance of preoperative assessment in predicting postoperative outcomes and guiding treatment decisions